Pyothorax in Antillean Manatee (Trichechus manatus) in Brazil - Attademo, Fernanda Löffler Niemeyer; Luna, Fábia de Oliveira; Sousa, Glaucia Pereira de; Freire, Augusto Carlos da Bôaviagem; Balensiefer, Deisi Cristiane; Oliveira, Radan Elvis Matias de (Acta Scientiae Veterinariae, 2020)
Background: Manatees are the most endangered aquatic mammals in Brazil. The current conservation scenario, together with their biological characteristics, raises concern with the future of this species. Pyothorax, also known as septic pleural effusion or pleural empyema, is characterized by the accumulation of a septic purulent exudate within the pleural space. Although this infection often has a multifactorial etiology, it is most commonly associated with respiratory tract disorders and trauma. Here, we report a case of pyothorax in a Antillean manatee (Trichechus manatus) held in captivity for acclimatization in Brazil. Case: A young, male Antillean manatee, aged 4 years and 11 months, measuring 227 cm in total length, and weighing 258 kg was held in captivity for acclimatization (natural environment) in Porto de Pedras in the State of Alagoas, Brazil. The animal died in February 2013 and was sent for necropsy at the CMA/ICMBio laboratory. The study was developed with authorisation from the Ethics Committee on Animal Use (License number 020/2009) and under the license SISBIO/ICMBio number 20685-1. Externally, the carcass of the animal showed swelling and bulging of the right antimere and purulent secretion from the right nostril. After external examination, a window was opened in the layers of skin, fat, and muscles from the level of the anus to the navel. Subsequently, the abdominal cavity was opened for inspecting the internal organs. The subcutaneous muscles had a slightly friable, swollen, and pale texture, in addition to petechial hemorrhage, suffusions, and marked edema of the subcutaneous tissue. The right hemidiaphragm was elevated, filling the abdominal and thoracic spaces. Depending on the elevation, all organs were moved to the left antimere. After dissecting the surrounding structures and analyzing the causes for the increase in volume, it was observed that the right lung formed a structure containing a large amount of purulent exudate, which was delimited by the right hemidiaphragm. It had a length of 111 cm, width of 40 cm, and wingspan of 137 cm, starting from the first thoracic rib to the last lumbar rib, near the peduncle region. After making an incision in the right hemidiaphragm and visceral pleura, approximately 70 L of purulent exudate and caseous material were removed. Since the right lung was severely damaged, visualizing the pulmonary parenchyma was not possible, and only remains of the main right bronchus could be seen. Discussion: Domestic species, such as dogs and cats, when affected by pleural empyema, usually have a restrictive breathing pattern (shallow and rapid breaths) and fever. Interpreting the clinical signs may be difficult for manatees because of their slow metabolism. In the United States, 44 (6%) cases of pleural empyema were recorded in manatees from a total of 731 animals evaluated, and shock with boats was determined as the primary cause. In the present animal, no signs of bone fractures were found, suggesting that the infection may have been caused by the use of an orogastric tube or even acquired in the environment prepared for acclimation. Based on the pathognomonic macroscopic findings, one can conclude that the animal had a characteristic clinical picture of pleural empyema (pyothorax) associated with an infection of unknown origin. This situation resulted in complete degeneration of the right lung and massive thoracic and abdominal distensions, resulting in decreased expansion capacity of the left lung, making breathing impossible, thus leading to death.